Isolation of Arbutin from Leaves and Fruits of Buni (Antidesma Bunius L. Spreng) As Tyrosinase Enzym Inhibitor - Palensina, Gea Ocktiah; Rosita, Leni; Sagala, Zuraida (Bioinformatics and Biomedical Research Journal, 2021)
Several studies have shown that plant extractive substances have the potential as active compounds inhibiting the enzyme tyrosinase. Arbutin is an enzyme inhibitor of tyrosinase, known as a popular whitening agent used in cosmetics because of its effectiveness in overcoming skin hyperpigmentation. The purpose of this study was to conduct a qualitative and quantitative analysis of arbutin on Buni Leaves and Fruits (Antidesma bunius L. Spreng). The raw simplicia used are mature and young buni leaves, green, red and purple buni fruits. The extraction method is maceration using methanol as solvent. The initial screening for arbutin content was carried out using thin layer chromatography (TLC) and dichlormethan:methanol 50:50 used as mobile phase. Isolation of arbutin content was carried out using Preparative TLC with the same eluent. Qualitative and quantitative analysis were performed using High Pressured Liquid Chromatography (HPLC) with mobile phase of acetonitrile: water 60:40. The tyrosinase enzyme inhibition activity test was then carried out in vitro using 96-well microplate, l-tyrosine and l-dopa were used as substrate at a wavelength of 492 nm. The Rf values obtained ??for mature buni leaves and green buni fruits, respectively 0.61 and 0,62. The retention time of HPLC chromatogram respectively 2,784 minutes and 2,758 minutes. Arbutin levels in leaves and fruits are 7.9 mg / g and 2 mg / g. The activity of the enzyme tyrosinase of mature buni leaves on L-dopa and L-tyrosine substrate were respectively stated as IC50 values ??of 88.7191ppm and 101.33347 ppm. The activity of the enzyme tyrosinase of the green buni fruit on L-dopa and L-tyrosine substrate respectively stated IC50 values ??of 198,0293 ppm and 246,1296 ppm.